The importance of combined 24‐hour multichannel intraluminal impedance–pH monitoring in the evaluation of children with suspected laryngopharyngeal reflux. (24th October 2016) - Pavić, I.; Babić, I.; Čepin Bogović, J.; Hojsak, I.
Abstract : Objective: The aim of this study was to investigate the diagnostic usefulness of combined multichannel intraluminal impedance–pH (MII‐pH) monitoring in children with suspected laryngopharyngeal reflux (LPR). Design, setting and participants: A prospective study including children in whom, due to LPR suggestive symptoms, MII‐pH monitoring was performed at tertiary medical centre from February 2012 to July 2015. Interventions: All included children underwent same diagnostic protocol which included examination by single pulmonologist and ENT specialist and underwent 24‐hour MII‐pH monitoring. Main outcomes: Primary outcome was to determine MII‐pH characteristics of the children in whom LPR was suspected based on symptoms and ENT examination. Results: One hundred and four patients (mean age 8.9 years; range 0.4–17.9 years; male/female 57/47) participated in the study. In children with signs and symptoms suggestive of LPR, MII‐pH monitoring found the median incidence of proximal gastro‐oesophageal reflux (GER) of 15 (range 0–129), proximal acidic GER of 6.5 (range 0–66) and weakly acidic GER of 5 (range 0–102). There were significant positive correlations between the number of GER (proximal total, acidic and weakly acid) with Reflux Finding Score, Reflux Symptom Index and presence of eosinophils in nasal swabs. The only endoscopy ENT finding which significantly correlated with total proximal GER, acid proximal GER and weakly acidic proximal GER was arytenoid hyperaemia. Conclusion: Both acid and non‐acid reflux seem to have a significant role in the pathogenesis of LPR.